Offensive or amusing? The study on the influence of brand-to-brand teasing on consumer engagement behavioral intention based on social media - Ning, Yu-mei; Hu, Chuan; Tu, Ting-ting; Li, Dan (Frontiers in Psychology, 2022)
With the development of social media, advertising has migrated from traditional media to social media. Marketers are increasingly using social media's brand pages to actively create humorous dialogue interactions with other brands for brand communication to achieve positive business outcomes. Especially brand-to-brand's aggressive humor dialogue can also be an effective brand communication strategy. Based on benign violation theory, we have studied the influence mechanism and boundary condition of the brand-to-brand's aggressive humor styles (low-aggressive and high-aggressive) on consumer engagement behavioral intention in social media context. Through experiments, it is indicated that low-aggressive humor could promote consumer engagement behavioral intention more than high-aggressive humor. Benign appraisal mediates the relationship between low-aggressive humor and consumer engagement behavioral intention. Furthermore, brand personality not only moderates the effect of low-aggressive humor on consumer engagement behavioral intention, but also moderates the mediating role of benign appraisal between low-aggressive humor and consumer engagement behavior intention.